Drug-releasing mesenchymal cells strongly suppress B16 lung metastasis in a syngeneic murine model. Issue 1 (December 2015) - Pessina, Augusto; Leonetti, Carlo; Artuso, Simona; Benetti, Anna; Dessy, Enrico; Pascucci, Luisa; Passeri, Daniela; Orlandi, Augusto; Berenzi, Angiola; Bonomi, Arianna; Coccè, Valentina; Ceserani, Valentina; et al.
Abstract Background Mesenchymal stromal cells (MSCs) are considered an important therapeutic tool in cancer therapy. They possess intrinsic therapeutic potential and can also bein vitro manipulated and engineered to produce therapeutic molecules that can be delivered to the site of diseases, through their capacity to home pathological tissues. We have recently demonstrated that MSCs, uponin vitro priming with anti-cancer drug, become drug-releasing mesenchymal cells (Dr-MCs) able to strongly inhibit cancer cells growth. Methods Murine mesenchymal stromal cells were loaded with Paclitaxel (Dr-MCsPTX) according to a standardized procedure and their ability to inhibit the growth of a murine B16 melanoma was verified byin vitro assays. The anti-metastatic activity of Dr-MCsPTX was then studied in mice injected i.v. with B16 melanoma cells that produced lung metastatic nodules. Lung nodules were counted under a dissecting stereomicroscope and metastasis investigated by histological analysis. Results We found that three i.v. injections of Dr-MCsPTX on day 5, 10 and 15 after tumor injection almost completely abolished B16 lung metastasis. Dr-MCsPTX arrested into lung by interacting with endothelium and migrate toward cancer nodule through a complex mechanism involving primarily mouse lung stromal cells (mL-StCs) and SDF-1/CXCR4/CXCR7 axis. Conclusions Our results show for the first time that Dr-MCsPTX are very effective to inhibit lung metastasis formation. Actually, a cure for lung metastasis in humans is mostly unlikely and we do not know whether a therapy combining engineered MSCs and Dr-MCs may work synergistically. However, we think that our approach using Dr-MCs loaded with PTX may represent a new valid and additive therapeutic tool to fight lung metastases and, perhaps, primary lung cancers in human.